Cyclic polymers: synthesis, characteristics, and emerging applications. Issue 10 (8th August 2022) - Chen, Chaojian; Weil, Tanja
Abstract : This Review highlights recent advances in the synthesis, unique properties, and most prominent applications of cyclic polymers, and discusses the major challenges and future opportunities in this field. Abstract : Cyclic polymers with a ring-like topology and no chain ends are a unique class of macromolecules. In the past several decades, significant advances have been made to prepare these fascinating polymers, which allow for the exploration of their topological effects and potential applications in various fields. In this Review, we first describe representative synthetic strategies for making cyclic polymers and their derivative topological polymers with more complex structures. Second, the unique physical properties and self-assembly behavior of cyclic polymers are discussed by comparing them with their linear analogues. Special attention is paid to highlight how polymeric rings can assemble into hierarchical macromolecular architectures. Subsequently, representative applications of cyclic polymers in different fields such as drug and gene delivery and surface functionalization are presented. Last, we envision the following key challenges and opportunities for cyclic polymers that may attract future attention: large-scale synthesis, efficient purification, programmable folding and assembly, and expansion of applications.